Business Model Canvas (BMC) Approach for Ecotourism Development Based on Islamic Boarding School Community (Case: Cipeujeuh Valley, Darul Arqam Muhammadiyah Islamic Boarding School) - Al-Sakina, Nashiha; Yustiana, Yooce; Furqan, Alhilal (3BIO: Journal of Biological Science, Technology and Management, 2024)
This study investigates the potential for ecotourism in Cipeujeuh Valley, which is situated near the Darul Arqam Muhammadiyah Islamic boarding school in Garut Regency. The research examines the factors that drive tourists to visit the area, the level of community engagement, and the development of a community-based ecotourism business model. The data was gathered using descriptive statistics, the Ecotourism Opportunity Spectrum (ECOS) framework, and rapid rural appraisal techniques. The results indicate that Cipeujeuh Valley has intermediate ecotourism spectrum, with push factors such as sports and adventure, recreation and relaxation, social status, and quality time, and pull factors including nature and the local community, and enjoying facilities. The community is generally receptive to ecotourism development, with 61.3% expressing interest and 38.7% not. The study suggests that educational institutions, communities, organizations, and families can be targeted through a business model canvas that offers unique environments, sustainable resource use, community empowerment, educational tourism, and economic development. Key resources include natural attractions, religious and local wisdom activities, infrastructure, and a skilled workforce, while key activities involve nature-based and community-based tourism experiences.